The Influence of Forming Effects on The Bending Crush Behavior of Top-Hat Thin–Walled Beams - Sigit Puji Santosa; Nguyen Van Nhat Vu; Leonardo Gunawan; Annisa Jusuf (Mesin, 2016)
This paper presents a study on the effects of forming process of a top–hat thin–walled beams to its bending crush resistance under dynamic bending load. The thin–walled beam was formed using a one step deep drawing. HyperForm software simulated the forming process and mapped its effects such as thickness variations and residual plastic strains in to the crash analysis models. Then the dynamic bending crush analysis was carried out using LS–DYNA by using the geometry and materials data obtained from the forming analysis results. For each material model, the analyses were carried out for model with and without the forming effects. The bending crush behavior of the top–hat thin–walled beams were then analyzed to compare between the simulations with and without forming effects. The results show that by incorporating the effect of forming process, the bending crush resistance of the thin–walled beams is increase by 4.7%. The introduction of strain rates to the material model increases even further on the bending crush resistance of the thin–walled beam.